Penerapan Media Audio Visual Berbasis Powtoon Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPAS - Fida Nuraisyah; Arief Hidayat Afendi; Nur Asyiah (CV. ULIL ALBAB CORP, 2024)
This study discusses the application of learning media in improving the learning outcomes of IPAS fourth grade students of SD Negeri 1.Gebang. This study aims to determine whether the use of powtoon-based audio-visual media can improve learning outcomes in IPAS subjects. The method used is classroom action research using the cycle model of Kemmis and Taggart which consists of 2 cycles. The subjects of this study were 36 students. data collection techniques include observation, learning outcomes tests and documentation. The research instruments used teacher activity observation sheets and student activity observation sheets and written tests at the end of learning. The results showed an increase in activity and learning outcomes of students in Natural and Social Sciences subjects. This is evidenced by the increase in teacher activity in cycle I of 73.75% increased by 12.5% in cycle II to 86.25% and student activity in cycle I of 68.75% increased by 16.25% in cycle II by 85%. The increase in learning outcomes can be seen from the increase in the average of each cycle. In the pre-cycle, the average score was 54 which increased to 76 in cycle I then increased to 85.14 in cycle II. This shows that the application of powtoon-based audio-visual media can improve the learning outcomes of IPAS fourth grade students of SD Negeri 1 Gebang.